Mapeamento dos serviços de saúde aos usuários de cateterismo urinário: desafios para a prática avançada de enfermagem - Castilho, Sofia Selpis (Universidade Federal de São Carlos, 2023)
To map and to identify the material distributed in the health care network to urinary catheter users in a municipality in the state of São Paulo, Brazil. Method: Quantitative, descriptive-exploratory study, carried out with supervisors and/or managers of health services and a unit of distribution of materials used by urinary catheter users. Data were collected using a questionnaire and an interview via electronic form and analyzed by descriptive statistics. Results: Health services to urinary catheter users were mapped in five health regions: health centers, family health units, outpatient clinics, specialized centers, hospitals, and emergency care units. Intermittent catheter and indwelling catheter were the distributed materials, along with other essential materials. Conclusion: The study shows the high number of distributed urinary catheters; primary health care was the service that directed the care from the materials distribution. It is concluded that mapping the provided care allows for understanding the provided care as well as fostering future studies addressing healthcare network strategies for users of urinary catheter.
Mapping of health services to urinary catheter users: challenges for the advanced nursing practice
Keywords: Serviços de saúde; Enfermagem; Cateterismo urinário; Sistema único de saúde; Atenção à saúde; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM MEDICO-CIRURGICA